The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/v11060566
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of PCR Proof of Parvovirus B19 Genomes in Endomyocardial Biopsies of Patients Presenting with Myocarditis or Dilated Cardiomyopathy

Abstract: Background: Diverse viral infections have been associated with myocarditis (MC) and dilated cardiomyopathy (DCM). In this meta-analysis, we summarize the published results on the association of parvovirus B19 (B19V) genomes with human MC/DCM versus controls. Methods: n = 197 publications referring to B19V and MC or DCM were retrieved using multiple PubMed search modes. Out of these, n = 29 publications met the inclusion criteria with data from prospective analyses on >10 unselected patients presenting with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 63 publications
0
10
2
1
Order By: Relevance
“…Our study revealed the presence of actively replicating B19V among 12.5% (2/16) of patients with DCM and 20% (1/5) of patients with eosinophilic myocarditis, while it was not detected in patients with a clinical diagnosis of lymphocytic myocarditis (viral or non-viral). The prevalence of B19V among patients with DCM or myocarditis in our cohort is considerably lower than the prevalence quoted in previous reports 18 , 47 . A recent meta-analysis demonstrated that the prevalence of B19V in endomyocardial biopsies of patients with myocarditis or DCM (45.5%) was not significantly different than its prevalence in control tissues (37.5%), which supports the notion of B19V being a bystander virus as opposed to a causative agent for such conditions 47 , 68 .…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…Our study revealed the presence of actively replicating B19V among 12.5% (2/16) of patients with DCM and 20% (1/5) of patients with eosinophilic myocarditis, while it was not detected in patients with a clinical diagnosis of lymphocytic myocarditis (viral or non-viral). The prevalence of B19V among patients with DCM or myocarditis in our cohort is considerably lower than the prevalence quoted in previous reports 18 , 47 . A recent meta-analysis demonstrated that the prevalence of B19V in endomyocardial biopsies of patients with myocarditis or DCM (45.5%) was not significantly different than its prevalence in control tissues (37.5%), which supports the notion of B19V being a bystander virus as opposed to a causative agent for such conditions 47 , 68 .…”
Section: Discussioncontrasting
confidence: 90%
“…The prevalence of B19V among patients with DCM or myocarditis in our cohort is considerably lower than the prevalence quoted in previous reports 18 , 47 . A recent meta-analysis demonstrated that the prevalence of B19V in endomyocardial biopsies of patients with myocarditis or DCM (45.5%) was not significantly different than its prevalence in control tissues (37.5%), which supports the notion of B19V being a bystander virus as opposed to a causative agent for such conditions 47 , 68 . It is noteworthy that of all three patients in our cohort positive for B19V (2 DCM and 1 eosinophilic myocarditis), at least one additional actively replicating virus was detected within the same tissue.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…In an observational study [18], a significant association of human bocaviruses to gastroenteritis is reported, thus further expanding their clinical involvement in addition to the established association with respiratory tract infections. In a systematic review and meta-analysis study [19], the significance of the detection of parvovirus B19 genomes in endomyocardial biopsies of patients presenting with myocarditis or dilated cardiomyopathy is discussed. This review should be regarded as a very useful contribution to a long debated and far from settled issue.…”
Section: The Articles In the Special Issuementioning
confidence: 99%